Experimental characterization of chalcopyrite ball mill grinding processes in batch and continuous flow processing modes to reduce energy consumption - Cesar Celis (Elsevier, 2021)
A mineralogy, rheology, and energy consumption-based experimental characterization of chalcopyrite ball mill grinding processes, in both batch and continuous flow processing modes, is carried out in this work. Accordingly, chalcopyrite ore samples are initially characterized in terms of mineralogical composition, particle size distribution, grindability characteristics, and work index. Next, a rheological characterization of actual and lab-created chalcopyrite mineral-slurries is performed. Finally, an energy consumption-based characterization of several chalcopyrite ball mill grinding processes is performed. The results from the initial mineralogical characterization indicate ore samples featuring 5% chalcopyrite. These results also highlight that 80% of the particles present in the chalcopyrite head ore have a diameter smaller than 1386 μm. In addition, they indicate that the Bond ball mill work index is equal to 15.3 kWh/ton, which corresponds to a mineral with the presence of chalcopyrite. The rheological characterization related results indicate that all actual and lab-created mineral-slurries exhibit a shear thinning rheological behavior. These results also show that, because of the higher number of particle interactions, the slurries’ apparent viscosity increases with the increase in their solids content. Finally, the energy consumption-based characterization results emphasize that energy consumption is more significantly affected by mill speed than by slurry solids content. Indeed, for the same percentage of mass passing through a 200 mesh, it is found that the specific grinding energy decreases with both the increase in slurry solids concentration and the decrease in mill speed. The results obtained in this work are consistent with findings made in previous studies.